NEGOSIASI IDENTITAS PENARIK BECAK WANITA - Analisa Analisa; Netty Diah Kurniasari (Jurnal Komunikasi, 2015)
The purpose of the study is to describe the negotiation of gender identity of woman’s pedicab drivers in their social life. Stigmatize or opinions among people that woman only works such as 3M (cooking, make up, and give birth). Otherwise in perak Surabaya, and bangkalan Madura there are some women works as pedicap drivers. It is a proof that woman not only able to work in domestic but also public worksThe study applies qualitative descriptive analysis with data collecting methods by interviews, observation and documentation. Data analysis technique used is data reduction, data providing and conclusion. Data validity technique applied is source of triangulation source for data validity cheeking in which the informants are selected by using purposive sampling method.The results of the study shows that identity negotiations of woman’s pedicab driver are receive although pedicap women adopt the values of pedicap man. Furthermore there is something unfair with genders inequality/ inequity in revealing identity which is happened to woman’s drivers in their social life. Such us , Stereotipe, Subordinasi, Marginalization, Double Burden and Violence.Keywords: Negotiation Identity, Identity, Gender Concept, and Feminist Eksistensialis.